4x-y=3y+7x+8y

Simple and best practice solution for 4x-y=3y+7x+8y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-y=3y+7x+8y equation:


Simplifying
4x + -1y = 3y + 7x + 8y

Reorder the terms:
4x + -1y = 7x + 3y + 8y

Combine like terms: 3y + 8y = 11y
4x + -1y = 7x + 11y

Solving
4x + -1y = 7x + 11y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
4x + -7x + -1y = 7x + -7x + 11y

Combine like terms: 4x + -7x = -3x
-3x + -1y = 7x + -7x + 11y

Combine like terms: 7x + -7x = 0
-3x + -1y = 0 + 11y
-3x + -1y = 11y

Add 'y' to each side of the equation.
-3x + -1y + y = 11y + y

Combine like terms: -1y + y = 0
-3x + 0 = 11y + y
-3x = 11y + y

Combine like terms: 11y + y = 12y
-3x = 12y

Divide each side by '-3'.
x = -4y

Simplifying
x = -4y

See similar equations:

| 3x+4(-2+2x)=25 | | 2.7=0.7*x+0.9 | | y^3=x+8 | | -2(x-9)-27=-9 | | -4y+x=-6 | | -8-8n=-7(7n+7) | | 3x-2=2x-24 | | y=7-x^3 | | -3m-4m-3(-10m-7)= | | 4(1-5x)-4(-4-6x)=x-4+3x-5 | | -7k-10k-2(3k-4)= | | 6(x-12)=x+7(1+12x) | | 42=-7d | | 6x+10=-22-10 | | 5x+1*5x+1=7 | | 2(3x+2)=6x+4 | | 21+2= | | 5(6+4n)=11(3n+11) | | x^3-4x+8=0 | | 3/2x+8 | | 1/2(x+6)=11 | | 3(x+2)/4=2x+1 | | 9(x+9)=-6(x-1) | | 2/3x-15=28-1/3x | | 4x+8-3x=8x+6-7x | | 15y=14(y+11) | | 9(x-2)/6=3(x+3)/7 | | w-3/7=-3/8 | | -6(-5-4x)=-5(12-3x) | | 2x-3=5+4x | | -6-20=-8-7x-6 | | -a-5=1 |

Equations solver categories